Learning SAS : a computer handbook for econometrics : a guide to programming for Griffiths/Hill/Judge Learning and practicing econometrics, and Judge/Hill/Griffiths/Lütkepohl/Lee Introduction to the theory and practice of econometrics - Hill, R. Carter (New York : John Wiley and Sons, 1993)
Getting started with the SAS system. Some Basic ideas: statistical concepts for economists. Statistical inference I, II. Simple regression...
Keywords: Computer programs; Conometrics; SAS; Econometrics -- Computer programs; SAS (Computer file)